2017
DOI: 10.1136/bmjopen-2017-018509
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and laboratory test ordering in Northern Portuguese Primary Health Care: a cross-sectional study

Abstract: ObjectivesTo characterise the test ordering pattern in Northern Portugal and to investigate the influence of context-related factors, analysing the test ordered at the level of geographical groups of family physicians and at the level of different healthcare organisations.DesignCross-sectional study.SettingNorthern Primary Health Care, Portugal.ParticipantsRecords about diagnostic and laboratory tests ordered from 2035 family physicians working at the Northern Regional Health Administration, who served approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
7
0
4
Order By: Relevance
“…Os exames laboratoriais apoiam 70% dos diagnósticos e das decisões de tratamento (2) , sendo os mais solicitados e também os responsáveis por maior gasto (3) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Os exames laboratoriais apoiam 70% dos diagnósticos e das decisões de tratamento (2) , sendo os mais solicitados e também os responsáveis por maior gasto (3) .…”
Section: Introductionunclassified
“…Os exames mais solicitados se repetem em diversos estudos: ácido úrico, ALT (alanina aminotransferase), AST (aspartato aminotransferase), colesterol total, creatinina, eletrólitos, GGT (gamaglutamil transferase), glicemia, HDL (high-density lipoprotein cholesterol), hemograma, microalbuminúria, triglicerídeos, TSH (hormônio estimulante da tireoide), e ureia (1,3) .…”
Section: Introductionunclassified
“…Several studies suggested that unnecessary and inappropriate utilization of laboratory services is closely linked to inter-practitioner variability in test requesting. [6][7][8] Despite the increased availability of clinical management guidelines promoting harmonization of the use of laboratory tests, there is still substantial variation in test utilization among general practitioners. 7,9 These differences appear to be unrelated to demographic characteristics of patient populations, socio-economic status of GP practices, disease prevalence or clinical outcome indicators.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Despite the increased availability of clinical management guidelines promoting harmonization of the use of laboratory tests, there is still substantial variation in test utilization among general practitioners. 7,9 These differences appear to be unrelated to demographic characteristics of patient populations, socio-economic status of GP practices, disease prevalence or clinical outcome indicators. 6,7,10,11 Even if some of these variables have been shown to have an effect on test ordering patterns, the variation in requesting rates is so large that it can only be explained by differences in attitudes towards the use of laboratory tests of individual practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation